Preservation of Malaysian handicraft to support tourism development - Hassan, Hasliza; Siow-Kian, Tan; Rahman, Muhammad Sabbir; Sade, Abu Bakar (Inderscience, 2016)
Handicraft depicting local culture and heritage is able to embellish tourism development. Instead of depending solely on government initiative, development of the handicraft industry can be driven by entrepreneurs. Handicraft skills among people in rural areas can benefit greatly from enhanced entrepreneurial skills, especially as a means to develop the overall socio-economic status. This research is based on an analysis of secondary findings on challenges in developing the handicraft industry among local entrepreneurs, particularly those from rural areas. It also explores the prospects of preserving cultural identity through transforming the handicraft industry.The value of traditional handicraft can be preserved through enhancing the role of entrepreneurs but young people seem to lack interest in the handicraft industry. This research suggests that society needs to change its perception to regard entrepreneurs dealing with handicrafts as a well-respected profession.